Persepsi Pasien Rawat Inap Terhadap Public, Personal dan Therapeutic Hospitality di Rumah Sakit Universitas Hasanuddin Tahun 2013 - Dessya Putri Ayu (Puslitbang Sinergis Asa Professional, 2019)
The background of this research was decreased by Indonesian citizens tend to choose medical tourism in neighboring countries such as Malaysia and Singapore, where hospitality is one of eksternal factor that causes it. Hospitality is a services provider to customer that which creates the impression by hosting and hospitableness. Hospitality in the health industries is divided into three such as public hospitality, personal hospitality, and therapeutic hospitality. The aims of this research is to describe the patient Inpatient unit perceptions with public hospitality, personal hospitality and therapeutic hospitality in Hasanuddin University Hospital. The method of this research is descriptive with devide class treatment using proportional stratified random sampling. Respondents of this research is 100 patients where patients undergoing treatment more than three days in Hasanuddin University Hospital.The result of this research showed that patient perception with public hospitality 56% good and 44% deficient, personal hospitality 66% good and 34% deficient, therapeutic hospitality 65% good and 35% deficient. Most respondents were undergoing treatment in Hasanuddin University Hospital has a good perception of the three hospitality although there are some complaints. Suggested for the hospital must improve the three hospitality in hospital, especially personal hospitality for patient.